Biomimetic periosteum combining BMP-2-loaded M2 macrophage-derived exosomes for enhanced bone defect repair - Ling, Feng; Bai, Jianzhong; Xie, Jile; Liu, Jie; Lu, Qifeng; Yuan, Lili; Li, Hongye; Qian, Zhonglai (Frontiers in Bioengineering and Biotechnology, 2025)
Bone defect repair continues to present a significant clinical challenge due to the limitations of traditional grafting techniques and the complexity involved in establishing a conducive regenerative microenvironment. In this study, we described the development of a multifunctional biomimetic periosteum based on electrospun gelatin methacryloyl (GelMA) membranes functionalized with bone morphogenetic protein-2 (BMP-2)-loaded M2 macrophage-derived exosomes. This engineered periosteum replicated the structural orientation and functional properties of natural periosteum, thereby providing a synergistic approach to promoting bone regeneration. Our findings indicated that the biomimetic periosteum served as a biocompatible scaffold that supported cell adhesion, proliferation, and differentiation. The incorporation of M2 macrophage-derived exosomes facilitated the creation of an anti-inflammatory immune microenvironment by polarizing macrophages towards the M2 phenotype, while the sustained release of BMP-2 enhances osteogenic differentiation and mineralization. In vivo experiments using a rat cranial defect model demonstrated that the BMP-2@Exo-GelMA membrane significantly accelerated bone defect repair, achieving superior outcomes in new bone formation and vascularization compared to control groups. This study underscored the potential of integrating immunomodulatory and osteoinductive strategies to develop next-generation biomaterials for bone tissue engineering. The biomimetic periosteum represented a promising therapeutic approach for addressing critical-sized bone defects and advancing clinical practices in bone regeneration.